2021
DOI: 10.1097/corr.0000000000002094
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Minimally Important Changes of Four Commonly Used Patient-reported Outcome Measures for 36 Hand and Wrist Condition-Treatment Combinations?

Abstract: Background Patient-reported outcome measures (PROMs) are frequently used to assess treatment outcomes for hand and wrist conditions. To adequately interpret these outcomes, it is important to determine whether a statistically significant change is also clinically relevant. For this purpose, the minimally important change (MIC) was developed, representing the minimal within-person change in outcome that patients perceive as a beneficial treatment effect. Prior studies demonstrated substantial differences in MIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
2
23
1
Order By: Relevance
“…Patients completed the Michigan Hand Outcomes, Patient-rated Wrist/Hand Evaluations, or the Boston Carpal Tunnel Questionnaire depending on the presence of finger or thumb, wrist, or nerve conditions, respectively. Although the authors determined specific MIC values for condition-treatment sets using different patient-reported outcome measures [4], they also determined that MICs differ based on the condition-treatment combination and context. The knowledge of context-specific MICs for common condition-treatment scenarios may aid shared decision-making in treatment.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 2 more Smart Citations
“…Patients completed the Michigan Hand Outcomes, Patient-rated Wrist/Hand Evaluations, or the Boston Carpal Tunnel Questionnaire depending on the presence of finger or thumb, wrist, or nerve conditions, respectively. Although the authors determined specific MIC values for condition-treatment sets using different patient-reported outcome measures [4], they also determined that MICs differ based on the condition-treatment combination and context. The knowledge of context-specific MICs for common condition-treatment scenarios may aid shared decision-making in treatment.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Hoogendam et al [4] completed a major undertaking to help their patients understand treatments alternatives and stated that a patient “may feel that the investment of undergoing a more invasive treatment should yield greater improvement.” Our patients are the most important stakeholders in the healthcare system; others include employers, insurance companies, the pharmaceutical industry, orthopaedic device companies, and government. Although improvement or change in a condition, defined with outcome tool scores, can be calculated, perhaps less clear is a stakeholder’s characterization and understanding of “invasive” and “investment.”…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal clinically important difference (MCID) indicates the minimal within-person change in outcome patients perceive as beneficial. Hoogendam et al 15 have reported the MCID for the MHQ specifically in patients who underwent PIP arthroplasty. The MCID was set at 24 points on the pain subscale.…”
mentioning
confidence: 99%
“…The MCID was set at 24 points on the pain subscale. 15 The primary aim of our study was to assess the MHQ pain score after PIP arthroplasty, comparing preoperative scores to 3-and 12-month postoperative scores and calculating the percentage of patients reaching the MCID. The secondary aims were to assess the MHQ total and subscale scores and calculate the percentages of patients reaching the MCID of the MHQ subscales.…”
mentioning
confidence: 99%